Music Composition “Tresna Sih Rupaka” | Komposisi Musik “Tresna Sih Rupaka” - Putu Diky Wahyu Arjaya; I Made Dwi Andika Putra (GHURNITA: Jurnal Seni Karawitan, 2023)
Tresna means love or affection, Sih which means more meaning, and Rupaka which means both parents. Tresna Sih Rupaka is a concept depiction of the sincere affection of parents towards their children. Giving endless love, giving guidance to his son to provide provisions to be a supportive child. The concept is implemented into a work of Tabuh Kreasi by using gamelan Semar Pegulingan as Saih Pitu, the reason for using gamelan semar pagulingan saih pitu in order to play patet in accordance with the atmosphere and nuances to be achieved. The process of creativity used at this stage of creation uses methods written by I Wayan Diana Putra mentioned by Senen from the creation stage I Wayan Beratha who adheres to three processes namely, Nguping (imitation), Menahin (repair), and Ngelesin (smoothing). In its production this work no longer uses a tri-angga structure but uses sections, which in each section describe the affection of parents.